FC Portugal Rescue: high level coordination in the RoboCup rescue simulation - Lau, Nuno (2009)
This paper presents an overview of the RoboCup Rescue Simulation League and the rescue team FC Portugal. RoboCup Rescue Simulation is an international joint projectthat promotes research on distributed artificial intelligenceand intelligent robotics. It offers a comprehensive urbandisaster simulator, forums for technical discussions andcompetitive evaluation for researchers and practitioners. Thispaper explains the objectives of the league, the mechanics of the simulator system and the main challenges in the research conducting using RoboCup Rescue simulator. In this urban disaster simulator, heterogeneous teams of agents try to minimize damage to both people and urban property afterthe occurrence of an earthquake. The city is filled withburning buildings, trapped civilians, and blocked roads.Teams of simulated fire brigades, policeman and ambulances collaborate in order to face the disaster. In this context, an overview of FC Portugal’s rescue team is presented, including the strategic coordination layer of heterogeneous agents and implemented agent’s roles and sub-tactics. In order to show the research conducted using the Rescue simulator some of the most interesting league problems are discussed together with FC Portugal’s solutions. Results achieved in international competitions are also brieflypresented, with emphasis on the 2006 European championship in Eindhoven, which FC Portugal won.